ENVIRONMENT AND ITS EFFECTS ON EMPLOYEE PERFORMANCE OF PRATAMA MILLA HUSADA BOYOLALI CLINIC - Ipung Sri Purwanti Hery; Ni Putu Ayu Patma Dewantari (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2021)
The environment is an important factor in improving the performance. Apriyana’s study (2016) shows that employees are able to work optimally if they are supported by a good working environment. This study aims to determine the effect of the environment on employees performance. Sutrisno (2011) and Kasmir (2016) stated that a conducive working environment gives employees a sense of comfort in carrying out the work and improves their performance. By using the quantitative descriptive method, 43 respondents were taken by saturated technique sampling. Data was collected through a questionnaire as the instrument. Data analysis uses the Multicollinearity test, Heteroscedasticity test, Multiple Linear Regression test, t test and Determination test. The Multicollinearity test results obtained tolerance values ??greater than 0.10 meaning that the environment doesn’t occur multicollinearity so that the environment has a normal effect on performance. Heteroscedasticity test produces a significance value greater than 0.05, so that the environment has a constant effect on performance. Regression test of 0.292 indicates a positive effect environment. T test value of 3.305 and a significance level of 0.002 <0.05 shows that the environment has a significant effect on performance. The determination test of 0.465 means that the environment explains 46.5% of the effects of employee performance. The results of this study require the Pratama Milla Husada Boyolali Clinic to improve a safe and comfortable working environment to achieve the employee performance’s improvement. Keywords: Environment, Employee Performance, Pratama Milla Husada Clinic